Gastroschisis and young mothers: What makes them different from other mothers of the same age? - Rittler, Mónica (2015)
BACKGROUND: Although young maternal age has been identified as a risk factor for gastroschisis, its role remains undisclosed. To our knowledge, the differences between young mothers of infants with gastroschisis and young mothers of infants with other pregnancy outcomes have not been established. The aim of this work was to compare characteristics of young mothers whose newborn had gastroschisis with same aged mothers of malformed and nonmalformed control infants, diagnosed within the ECLAMC maternity hospital network. METHODS: Data base records of live and stillborn infants of one of three groups (with isolated gastroschisis, with 1 of 5 other isolated birth defects, and nonmalformed), and whose mothers were younger than 20 years, were selected. Secular trends were obtained for all birth defects; frequencies and odds ratios (OR) of demographic and reproductive variables were compared among the 3 groups. Significantly associated variables were adjusted with a multivariate regression. RESULTS: The association was higher with gastroschisis 1) than with other birth defects for African ancestry, smoking, adequate prenatal control and diagnosis 2) than with nonmalformed controls for maternal illnesses and alcohol 3) and than both for previous pregnancy loss and medication, mainly sex hormones. After adjustment, only previous pregnancy loss maintained its significance when compared with malformed (OR = 2.34; 1.37-3.97; P = 0.002), as well as with nonmalformed (OR = 3.43; 2.07-5.66; P < 0.001) controls. CONCLUSION: A previous pregnancy loss was identified as the main risk factor for gastroschisis, while an increased use of sex hormones, perhaps related to the previous loss, could trigger a disruptive mechanism, due to their thrombophilic effect.